Perioperative Management of Hyperlipidemia Medications - Renew, Johnathan R. (Current Clinical Pharmacology, 2017)
Background: Coronary artery disease is a common comorbidity encountered during the perioperative period. Whether patients are scheduled for cardiac or noncardiac surgery, this cardiovascular disease must be addressed in the preoperative period to decrease the accompanying risks and potential postoperative problems. Lipid-lowering medications are often used to treat hyperlipidemia, a risk factor for the development of atherosclerosis and coronary artery disease. Objective: To discuss the medications most commonly used to treat hyperlipidemia and to describe strategies for handling these treatment regimens in the perioperative period. Method: An online search of studies and review articles was conducted through PubMed and Medline that addressed pharmacology and perioperative management of hyperlipidemia medications. Results: Statins are the most commonly prescribed lipid-lowering agents, with benefits that extend beyond correcting lipid levels. However, statins can have clinically significant adverse effects that may necessitate the use of other lipid-lowering medications with different mechanisms of action. Alternative medications such as nicotinic acid and omega-3 fatty acids should be withheld in the preoperative period because these agents have been associated with hypotension and increased bleeding. Conclusion: Clinicians must be familiar with the various lipid-lowering agents because it is very likely they will encounter such medications during preoperative visits.
Keywords: perioperative care